The effects of detraining and retraining on swimming propulsive force and blood lactat - Hsu, K. M.; Hsu, T. G. (Medicine & Science in Sports & Exercise, 1999)
The effects of detraining and retraining on 50 and 400-m performance, arm stroke propulsive power, lactate, and lactate dehydrogenase in crawl stroke swimming were investigated. Male college swimmers (N = 18) detrained for 85 days by not performing any swimming. Retraining consisted of covering between 3,500-6,000 m per day for 91 days. After detraining 50-m times regressed 3.4% and 400-m times regressed by 7%. Arm stroke propulsive power regressed by 12%. Peak lactate for the 400 swim was 22% lower. After retraining, 50-m times and arm-stroke propulsive power had not returned to the levels exhibited before detraining. Lactate dehydrogenase was unaltered by either detraining or retraining. It was concluded that recovering lost training effects takes much longer than the period of time in which they were lost. Implication: Recovering training effects takes much longer than losing them through detraining. It would be wise to avoid detraining.